A near infrared optical reflector using one-dimensional photonic crystal structure containing chalcogenide glasses - Srivastava S.K.; Awasthi S.K.; Srivastava S.K.; Ojha S.P. (My University, 2025)
The reflectivity of one-dimensional chalcogenide photonic crystal (CGPC) structure with the first order reflection band in near infrared (NIR) region is theoretically studied. Sb-Se and Ge-S chalcogenide glasses are used as high and low refractive index layers respectively, because these materials have zero absorption in NIR region. The transfer matrix method (TMM) is employed to calculate the reflective spectra of the proposed structure. The theoretical results of reflective spectra of bulk chalcogenide materials with the composition of Sb40Se60 and Ge30S70 for 4, 8, 12 and 15 layers and thicknesses of 117 nm and 183 nm respectively, at normal incidence, are close agreement with the experimental results. Furthermore, by increasing the number of layers of Sb40Se60 and Ge30S70, the reflection bands can be enhanced in the wider range of the NIR region for the polarization at different angles and thus the broadband omnidirectional reflector can be designed. © 2010 Tianjin University of Technology and Springer-Verlag Berlin Heidelberg.